2023
DOI: 10.1136/bcr-2022-251273
|View full text |Cite
|
Sign up to set email alerts
|

Complete response of a large basosquamous carcinoma following treatment with cemiplimab and vismodegib

Abstract: The anti-PD-1 antibody cemiplimab has demonstrated effectiveness in the setting of locally advanced basal cell carcinoma (BCC) and squamous cell carcinoma. We describe a case of a large, locally invasive basosquamous carcinoma, an aggressive type of BCC, invading the left sternocleidomastoid muscle with near compression of the left internal jugular vein producing a severe anaemia secondary to ulceration and chronic blood loss. The patient was initially started on vismodegib monotherapy but failed to respond. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…On the other hand, the largest published cohort study of 1675 patients suggests that vismodegib is not associated with an increased risk of developing SCC, while a systematic and a narrative review of the literature concluded that the available evidence does not justify an association between vismodegib and the development of SCC [68,69]. In addition, there are very recent case reports involving a total of five patients that provide preliminary evidence that vismodegib may be effective in difficult-to-treat BSC (Table 1) [69][70][71]. In all cases, the lesions did not "transform" into pure squamous cell tumors but, on the contrary, regressed completely, and in two cases remission was maintained over a very long period [69][70][71].…”
Section: Sonic Hedgehog Inhibitors (Hhis)mentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the largest published cohort study of 1675 patients suggests that vismodegib is not associated with an increased risk of developing SCC, while a systematic and a narrative review of the literature concluded that the available evidence does not justify an association between vismodegib and the development of SCC [68,69]. In addition, there are very recent case reports involving a total of five patients that provide preliminary evidence that vismodegib may be effective in difficult-to-treat BSC (Table 1) [69][70][71]. In all cases, the lesions did not "transform" into pure squamous cell tumors but, on the contrary, regressed completely, and in two cases remission was maintained over a very long period [69][70][71].…”
Section: Sonic Hedgehog Inhibitors (Hhis)mentioning
confidence: 99%
“…In addition, there are very recent case reports involving a total of five patients that provide preliminary evidence that vismodegib may be effective in difficult-to-treat BSC (Table 1) [69][70][71]. In all cases, the lesions did not "transform" into pure squamous cell tumors but, on the contrary, regressed completely, and in two cases remission was maintained over a very long period [69][70][71]. Despite these positive data, in one case of basosquamous carcinoma treated with vismodegib, the drug had to be discontinued due to adverse effects before its efficacy could be evaluated [72].…”
Section: Sonic Hedgehog Inhibitors (Hhis)mentioning
confidence: 99%
See 1 more Smart Citation